Spatial data management [ - Mamoulis, Nikos (San Rafael, Califonia : Morgan & Claypool Publisher, 2012)
Spatial database management deals with the storage, indexing, and querying of data with spatial features, such as location and geometric extent. Many applications require the efficient management of spatial data, including Geographic Information Systems, Computer Aided Design, and Location Based Services. The goal of this book is to provide the reader with an overview of spatial data management technology, with an emphasis on indexing and search techniques. It first introduces spatial data models and queries and discusses the main issues of extending a database system to support spatial data. It presents indexing approaches for spatial data, with a focus on the R-tree. Query evaluation and optimization techniques for the most popular spatial query types (selections, nearest neighbor search, and spatial joins) are portrayed for data in Euclidean spaces and spatial networks.
1. Introduction -- 2. Spatial data -- 3. Indexing -- 4. Spatial query evaluation -- 5. Spatial networks -- 6. Applications of spatial data management technology
Part of: Synthesis digital library of engineering and computer science
Includes bibliographical references (p. 119-132) and index
Keywords: Database management; Geospatial data; Spatial data infrastructures